EFFECTS OF (−)-EPICATECHIN AND DERIVATIVES ON NITRIC OXIDE MEDIATED INDUCTION OF MITOCHONDRIAL PROTEINS - Moreno-Ulloa, Aldo (2013)
Impaired mitochondrial function represents an early manifestation of endothelial dysfunction and likely contributes to the development of cardiovascular diseases (CVD). The stimulation of mitochondrial function and/or biogenesis is seen as a means to improve the bioenergetic and metabolic status of cells and thus, reduce CVD. In this study we examined the capacity of the flavanol (−)-epicatechin and two novel derivatives to enhance mitochondrial function and protein levels in cultured bovine coronary artery endothelial cells. As nitric oxide production by endothelial cells is suspected in mediating mitochondria effects (including biogenesis), we also examined the dependence of responses on this molecule using an inhibitor of nitric oxide synthase. Results indicate that the flavanol (−)-epicatechin and derivatives are capable of stimulating mitochondria function as assessed by citrate synthase activity as well as induction of structural (porin, mitofilin) and oxidative phosporylation protein levels (complex I and II). Effects were blocked by the use of the chemical inhibitor of the synthase thus, evidencing a role for nitric oxide in mediating these effects. The results observed indicate that the three agents are effective in enhancing mitochondria function and protein content. The effects noted for (−)-epicatechin may serve to explain the healthy effects on cardiometabolic risk ascribed to the consumption of cocoa products.